Shifting Interiority: Changing Encounters With Our Environment - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Interiority, 2020)
During COVID-19 pandemic, the whole world has witnessed and experienced dramatic changes in all aspects of life. As we adapt our everyday lives to restrictions and limitations to fight the pandemic, it also has become a trigger for us to rethink and re-position knowledge on spatial design disciplines. This Interiority issue compiles contributions that respond to a special call for papers that address these questions: How does the pandemic, including its impacts from lockdowns and physical distancing, affect how we think about interior and architecture? What lessons can we learn from this situation that we can use in future interior and architectural spaces and practices? How does the idea of interiority shift in this challenging situation?